Forecasting the Price Movement of Volatility Index using the Fuzzy Tsukamoto Method and Dstat Metric Evaluationindonesia - Utomo, Wahyu Cahyo; Saputra, Muh Aris (Generation Journal, 2023)
Volatility index is one of the assets traded in trading activities. In this activity there are two possibilities that can be done by traders, namely buy and sell actions. This is the main problem in forecasting in the world of finance. With these two opportunities, an analysis is needed to estimate the direction of price movement correctly. In addition in trading the subjectivity factor sees very high price movements. In a sense, each individual trader has his own assumptions. So a non-subjective analysis system is needed. Based on these challenges, this research will focus on forecasting with a non-subjective approach with fuzzy logic or more precisely Fuzzy Tsukamoto and Dstat metric as an evaluation of the level of correctness of the prediction direction. From the results that have been tested in the study, the Fuzzy Tsukamoto Method by reading the Relative Strength Index and Stochastic Oscillators indicators received an evaluation value that met the trading industry standards of 64.13%.